Sobre Gerardo Lara Cisneros, Gabriel Torres Puga, Miguel Rodrigues Loreunço y Susana Bastos Mateus (coords.), Inquisición y lenguaje, siglos XVI-XIX - Centella Zamora, María (El Colegio de México, A.C., 2025)
-